The Role Of Digital Financial Services In Accelerating Womens Economic Empowerment In Indonesia: What Is Left To The Learn - Nur Azizah, Siti; Annisa Nur Salam (Al-Mashrafiyah: Jurnal Ekonomi, Keuangan, dan Perbankan Syariah, 2024)
The rapid growth of digital financial services provides opportunities for advancing gender equality more broadly. This is because digital financial services (DFS) are increasingly accessible to homemakers who do not have bank accounts. So that can use it can use to reduce gender disparities in accessing finance and advance women’s economic empowerment (WEE) within their households and local economies, this study aims to examine the effect of digital financial services (DFS) on Women’s Economic Empowerment. This study uses descriptive statistical analysis. Descriptive statistics seek a complete and accurate description of a situation and are needed to identify the distribution and behavior of the data held. Collected the secondary data from various sources to study the role of digital financial services in Indonesia like 120 women who use smartphones, are homemakers and are active in social organizations in Indonesia, such as account holders who use digital payments to pay their electricity bills, pay motorbike bills and shop for various household needs. The results of this study indicate that the use of digital financial services has a positive effect on reducing the gender gap and on women’s economic empowerment.